Konsep Kebebasan di Mata Generasi Muda Muslim di Daerah Bandung dan Jakarta: Sebuah Studi Fenomenologi - Usman, Irianti; Utari, Riyanda; Suwandi, Firdaus Dwi; Yusron, Isman Rahmani (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2022)
This phenomenological study investigated the way three authentic Indonesian Muslims who live in Bandung and Jakarta gave meaning to the word freedom. Three informants were purposively selected to participate in the study: a 34-year-old Muslim businesswoman; married; and lives in Jakarta; a Muslim man, 36 years old, single, a lawyer who lives in Bandung; and a 21-year-old single man who is a sophomore at a private university in Bandung. In-depth interview was administered to obtain detailed and more comprehensive information about the participantsâ€™ thoughts and experiences.Â IPA (Interpretative Phenomenological Analysis) and Domain Analyses were utilized to analyze the data gathered. The study found that birth order, parenting styles, exposure to collectivist or individualistic value systems as well as Western concept of freedom, repentance or â€œTawbahâ€, and increased knowledge about Islam were strongly related to their meaning construction of the word freedom.